Implementasi Pendidikan Karakter pada Pembelajaran Biologi Kelas VIII di UPTD SMP Negeri 1 Mandrehe - Windia Juli Yanti Zai; Lusia Zebua; Agnes Renostini Harefa (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine: (1) strategies for implementing character education in schools; and (2) implementing the implementation of character education at UPTD Mandrehe 1 Public Middle School. This research is a qualitative descriptive study. Data collection was carried out by observation, interview and documentation techniques. Checking the validity of the data was carried out using a triangulation technique, namely by checking the information from interviews with documentation and observation. The results of the study show that the strategy for implementing character education at UPTD SMP Negeri 1 Mandrehe can be carried out through: integrating values ​​and ethics in subjects, internalizing positive values ​​that are instilled by all school members, habituation and training, giving examples and role models, creating an atmosphere of character in schools , and culture. The implementation of character education at UPTD SMP Negeri 1 Mandrehe is carried out through integration between character building and learning, school management, and extracurricular activities.